Des pouvoirs et des hommes : l'administration municipale de Montréal, 1900-1950 - Dagenais, Michèle, 1957- (Canadian public administration series., 2000)
Basing her work on extensive study of Montreal's city records, Dagenais gives us a view of city government from inside city hall, showing how the city's institutions really functioned. From 1900 to 1950, the municipal administration underwent a decisive transformation to become a modern bureaucracy. Dagenais explores the forces behind modernization by illuminating the roles played by city hall's main actors; elected officials, department heads and civil servants. Dagenais presents the municipal government from three perspectives. She first views it as a public administration whose history is marked by the numerous power struggles which brought elected officials into conflict with professional bureaucrats. Secondly, she sees it as a large enterprise which was notably influenced by modern management techniques, and finally she shows it to be a working environment shaped by professional relationships. Dagenais provides the first detailed history of a municipal administration in Canada, one that is particularly important as Montreal was at the economic and financial centre of Canada during this crucial period of urban and industrial development.